Assessing the Trade Potential of Agricultural Products Using the Stochastic Frontier Gravity Model and General Equilibrium Analysis - Zeng, Letian; Hassan, Asan Ali Golam (International Journal of Computational and Experimental Science and Engineering, 2025)
Consumers’ dietary habits have evolved significantly, with an increased emphasis on consuming healthy fruits and vegetables. Chinese agricultural products are also being sold more frequently within the Regional Comprehensive Economic Partnership (RCEP) area, which represents a substantial market for Chinese fruits and vegetables. However, despite this, China has not increased its exports of fruits and vegetables to RCEP countries, and this trend is reflected in the overall growth pattern. Consequently, the composition of China’s agricultural exports has undergone notable changes. Within the framework of the RCEP, China engages in trade with other member countries. However, the fruits and vegetables exported to these markets have not yielded significant economic benefits. This study may assist China and RCEP member nations in identifying effective strategies to facilitate the trade of fruits and vegetables as a means of economic cooperation. Furthermore, calculations of the agglomeration margin contribution over the sample period, using the logarithmic difference method, indicate that the growth in China’s fruit and vegetable exports to Malaysia, India, Indonesia, the Philippines, Japan, and New Zealand was primarily driven by the intensive margin, contributing 107%, 134%, 116%, 124%, 119%, and 132%, respectively.